Comparison among four triazole fungicides on growth and development of sheath blight of rice pathogen Rhizoctonia solani Kühn AG1-1A - Datta, Sambit; Dey, P.; Sarkar, A.; Tarafdar, J.; Chowdhury, A. (2016)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. The sheath blight of rice pathogen Rhizoctonia solani Kühn AG1-1A has long been known as a major crisis in global rice production. The present study aimed to compare the efficacy of four triazole fungicides at different doses on the growth and development of R. solani Kühn AG1-1A. Obtained results demonstrated inhibitory effects of all four fungicides on mycelial growth, sclerotia formation and biomass production of R. solani Kühn AG1-1A with significant variation among the treatment doses as well as fungicide molecules (p = 0.05). At the respective EC 50 doses all four fungicides inhibited cell wall degrading enzymes viz. invertase, cellulase, polygalacturonase and pectin lyase, of the sheath blight pathogen. The extent of inhibition of the enzymes significantly varied among the fungicides. It is important to note that in spite of having common mode of action, all four triazole fungicides demonstrated significant variation in their fungicidal efficacy on R. solani Kühn AG1-1A.